Pengaruh Rasio Gini, Indeks Pembangunan Manusia, dan Tingkat Partisipasi Angkatan Kerja terhadap Tingkat Pengangguran Terbuka Provinsi Lampung 2018-2023 - Olliviya Tri Hermanda; Andi Saputra; Fajar Muhammad Hasbi; Aidil Fitriansyah; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the influence of the Gini Ratio, Human Development Index (HDI), and Labor Force Participation Rate (LFPR) on the open unemployment rate in Lampung Province during the 2019–2023 period. The method used in the analysis is a fixed effect model approach with panel data regression, based on secondary data obtained from the Central Statistics Agency (BPS) of Lampung Province. The results of the partial test (t-test) indicate that the three independent variables—the Gini ratio, HDI, and LFPR—do not have a significant effect individually on the open unemployment rate in the region. However, the adjusted coefficient of determination (adjusted R²) value of 88.95% indicates that the model can explain almost all the variation that occurs in the open unemployment rate. This shows that although these variables are statistically insignificant in the model, theoretically they still have an important role in explaining unemployment dynamics in Lampung, along with other factors not yet included in the model. This research provides a strong basis for further analysis in formulating unemployment reduction policies, particularly in regions with economic and social characteristics such as Lampung. Recommendations from this study point to the need for a more comprehensive policy approach that considers other macroeconomic variables such as investment, industrial sector growth, and the quality of education and job training to effectively and sustainably reduce unemployment at the regional level.